Carrier-free, continuous primary beer fermentation - Pires, Eduardo J. (2014)
Developing a sustainable continuous fermentation reactor is one of the most ambitious tasks in brewing science, but it could bring great benefits regarding volumetric productivity to modern breweries. Immobilized cell technology is often applied to reach the large densities of yeast needed in a continuous fermentation process. However, the financial cost associated with the use of carriers for yeast immobilization is one of the major drawbacks in the technology. This work suggests that yeast flocculation could address biomass immobilization in a gas-lift reactor for the continuous primary fermentation of beer. Nearly 25 g dry wt L−1 of yeast was flocculated in the reactor before interruption of the fermentation. Stable sugar consumption and ethanol production (4.5% alcohol by volume) from an 11°P wort was evidenced. The key esters and higher alcohols measured in the young beer met the standards of a finished primary beer fermentation.